IMPROVEMENT OF LIFE SUPPORT SYSTEMS OF PASSENGER ROLLING STOCK: PATENT REVIEW - Kolesnykov, S. R. (Science and Transport Progress, 2021)
Purpose. Inventors and researchers of the world are focused on improvements of basic life support systems including provision of quality microclimate parameters in a car of the rolling stock. The research is aimed at reviewing and analyzing patents in the field of climate comfort, heating, ventilation and air conditioning (CCHVAC) of railway passenger cars (the chronological framework: 2011-2017 from the date of publication). Мethodology. During the study there were reviewed patents (foreign and domestic ones) in the field of CCHVAC in passenger vehicles, in particular railway cars, their optimization and ways of managing them. Patent search was carried out according to certain search criteria: keywords, time frames and in various patent systems of the world. An interdisciplinary approach was used. Findings. Based on the search results, 157 patents were found, 21 documents of which were selected for analysis. Patents are systematized into three groups: "New technical and technological solutions in systems and functioning facilities of HVAC ", "New and improved solutions for HVAC system management in a vehicle", "Air ozonation in passenger cars". It is established that all patents have one of the aspects that have solutions to the issues of more environmentally friendly, energy efficient and safe application of CCHVAC systems in railway transport. Originality. It was proved a high level of link penetration in various technical fields, which include patents with CCHVAC. It is established that it is characteristic for them to designate the majority of patent solutions for use not in the purely railway industry, but in transport in general. Practical value. Confirmation of the high level of link penetration in various technical fields will make it possible to reflect technical problems with CCHVAC and technologies for their solution throughout the world. This will contribute to a more intensive technological upgrade in the improvement of life support systems for passenger rolling stock.